2005
DOI: 10.1002/cvde.200506390
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Palladium from a Cylcopentadienyl‐allyl‐palladium Precursor on Si‐Based Substrates with Various Pretreatments: The Role of Surface Si–OH and Si‐H Species Studied by X‐Ray Photoelectron Spectroscopy

Abstract: The decomposition reactions of a metal-organic precursor for the CVD of Pd, (Cp)Pd(allyl), on Si substrates with various terminated surfaces have been studied using X-ray photoelectron spectroscopy (XPS). The XPS data show that mixed hydrogen/ hydroxyl-terminated Si surfaces exhibit the highest activity ascribed to acidic Si-OH groups for precursor decomposition, followed by the as-received Si surface. Clean, well-defined SiO 2 surfaces prepared in ultrahigh vacuum (UHV) exhibit the lowest activity for the Pd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The deposition was monitored using X-ray photoelectron spectroscopy (XPS) and infrared reflection absorption spectroscopy (IRRAS). We follow the approach taken in an earlier study, where the deposition of the Cp(allyl)Pd-precursor on Si substrates has been investigated . In this previous study, the amount of deposited Pd was small in the case of clean Si and SiO 2 , and a significant deposition was only observed when chemically available H species (SiH and mixed SiH and SiOH) were present on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition was monitored using X-ray photoelectron spectroscopy (XPS) and infrared reflection absorption spectroscopy (IRRAS). We follow the approach taken in an earlier study, where the deposition of the Cp(allyl)Pd-precursor on Si substrates has been investigated . In this previous study, the amount of deposited Pd was small in the case of clean Si and SiO 2 , and a significant deposition was only observed when chemically available H species (SiH and mixed SiH and SiOH) were present on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…During these investigations we have also found that the decomposition of Cp(allyl)Pd is initiated by hydroxyl groups on the carrier particle surface, and that changing the surface concentration of these OH groups leads to a proportional variation in the Pd dot density 5. In addition to its dissociation on functional surface groups,6 the precursor molecule Cp(allyl)Pd is known to decompose on previously deposited elemental Pd via an autocatalytic mechanism 7, 8. Autocatalytic decomposition is typical for (noble) metal‐organic compounds and accelerates the deposition process considerably 9, 10.…”
Section: Introductionmentioning
confidence: 94%
“…Second, water is often used as the solvent for the Mo precursors, but it is preferentially adsorbed on the surface of alumina, leading to the condensation of the precursor solution and thus a low degree of dispersion. [17,18] In comparison with other methods, MOCVD uses low deposition temperatures and achieves fast growth rates. [17] Furthermore, the method is not influenced by the pore volume and isoelectric point (IEP) of the substrate, or the solubility of the precursor.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] In comparison with other methods, MOCVD uses low deposition temperatures and achieves fast growth rates. [17] Furthermore, the method is not influenced by the pore volume and isoelectric point (IEP) of the substrate, or the solubility of the precursor. A high degree of dispersion can be achieved by CVD due to reaction between the functional groups of the precursor and the substrate forming strong bonds followed by decomposition at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%